"Where u from, who u wit?!" Black Pride Festivals as Itinerant Hospitality. - SMITH, CHRISTOPHER G. (Journal of Canadian Studies)
This article examines the phenomenon of Black Pride festivals. Initially intended as a form of community building during the HIV/AIDS crisis in the 1990s in select cities, Black Pride is both a celebration of Black lesbian, gay, bisexual, and transgender + (LGBT+) life and a space for political organizing. The model of Black Pride would be adopted throughout the United States and, internationally, in the United Kingdom and South Africa. While there are no "official" Black Pride festivals in Canada, there is a long-standing history of diasporic travel by Black LGBT+ Torontonians that have sought out these festivals as a site of affirmation of their identities and experiences. Blockorama, a one-day cultural festival that celebrates Black LGBT+ individuals during the Pride Toronto festivities, shares a similar history. Now in its twenty-first year, the story of Blockorama illustrates the challenges of visibility and recognition faced by Black LGBT+ communities within broader LGBT+ communities. As a snapshot from my current ethnographic and archival research on Black Pride, this analysis takes the form of a transnational comparison of the structural and political challenges faced by organizers of these events. Of particular concern is the confluence of anti-Black racism and the homonormative political priorities LGBT+ leaders that have shaped "mainstream" Pride festivals, rendering them increasingly corporate driven. Thus, this article specifically attends to the relationship between the spatial regulation and surveillance of Black LGBT+ bodies when moments of celebration are enacted in spaces that are seen as being "out of place." Conceptually, these moments of disruption are understood as an "itinerant hospitality" that engenders spaces of conviviality between Black LGBT+ communities and the individuals who cultivate their identities often in transit.